The effectiveness of leadership behavior among academician of Universiti Teknologi MARA Terengganu - Vadeveloo, Thenmolli; Ngah, Nor Syamaliah; Jusoff, Kamaruzaman (Canadian Research & Development Center of Sciences and Cultures, 2009)
People in organizations develop in their minds an implicit theory of leadership describing how an effective leader should act, and a leader prototype or mental image of what characteristics of effective leader should have. This paper aims to empirically determine the level of leadership effectiveness and leaders’ behavior from subordinates’ perception. This study is a cross-sectional research by distributing a set of questionnaire to academicians at local university, Universiti Teknologi MARA, Terengganu. A sample of 128 of academicians from seven faculties responded to a questionnaire which measured the leadership effectiveness and leaders’ behavior. Decision making, leadership performance, personal characteristics and communication skill are identified as the most important areas for effective leaders’ behavior. Leadership effectiveness model was adopted from Cumming. The findings show that the score for leadership effectiveness is the highest, followed by decision-making skill, leadership performance, communication skill and personal characteristic are significantly positive correlated to leadership effectiveness. Leadership effectiveness has been significantly explained by the four independent variables that are leadership performance, decision making skill, communication skill and personal characteristic.